Long-term accumulation and microdistribution of uranium in the bone and marrow of beagle dog - Arruda-Neto, JDT; Guevara, MVM; Nogueira, G. P.; Taricano, I. D.; Saiki, M.; Zamboni, C. B.; Bonamin, L. V.; Camargo, S. P.; Cestari, A. C.; Deppman, A.; Garcia, F.; Gouveia, A. N.; et al. (Taylor & Francis Ltd, 2004)
The accumulation and microdistribution of uranium in the bone and marrow of Beagle dogs were determined by both neutron activation and neutron-fission analysis. The experiment started immediately after the weaning period, lasting till maturity. Two animal groups were fed daily with uranyl nitrate at concentrations of 20 and 100 mug(-1) food. of the two measuring techniques, uranium accumulated along the marrow as much as in the bone, contrary to the results obtained with single, acute doses. The role played by this finding for the evaluation of radiobiological long-term risks is discussed. It was demonstrated, by means of a biokinetical approach, that the long-term accumulation of uranium in bone and marrow could be described by a piling up of single dose daily incorporation.